Analisis terhadap Legalisasi dan Perlindungan Hukum Korban Pemerkosaan yang Melakukan Aborsi Ditinjau dalam Prinsip Hak Asasi Manusia (Deposisi: Jurnal Publikasi Ilmu Hukum, 2025)
This research analyzes the legalization of abortion for rape victims in Indonesia from a human rights perspective, based on Law Number 36 of 2009 concerning Health and Government Regulation Number 61 of 2014 concerning Reproductive Health. The study aims to identify the forms of legal protection for rape victims who undergo abortion and to evaluate the extent to which its implementation aligns with human rights principles, particularly the rights to health, security, and dignity. Using a normative legal research method with a literature review, this study found that existing regulations have provided a legal basis for abortion in rape cases as a form of protection. However, its implementation still faces significant obstacles such as social stigma and limited access, which potentially hinder the fulfillment of victims' human rights.